Development of prediction models for carbapenem-resistant Klebsiella pneumoniae acquisition and prognosis in adult patients - Yao, Huijuan; Yang, Yu; Yao, Huimin; Bu, Shuhong; Li, Lixia; Wang, Fang; Zhang, Jian; Chen, Jihui (Frontiers in Pharmacology, 2024)
Objectives To explore the risk factors and clinical outcomes of carbapenem-resistant Klebsiella pneumoniae (CRKP) infection and establish nomograms to predict the probability of CRKP infection and mortality in adult patients. Methods Patients infected with KP from August 2019 to April 2021 in a tertiary hospital in Shanghai were enrolled. Risk factors associated with CRKP and 30-day mortality were identified using multivariate logistic regression analysis and Cox regression analysis. Results Overall, 467 patients with KP infection were enrolled, wherein 210 (45.0%) patients were infected with CRKP and 257 (55.0%) patients with carbapenem-susceptible K. pneumoniae (CSKP). Five factors, namely Charlson’s Comorbidity Index (CCI) ≥ 3, the use of central venous catheterization, prior hospitalization during the 3 months before infection, and previous exposure to carbapenems and broad-spectrum β-lactams, were found to be independently associated with CRKP infection. Based on these parameters, the nomogram showed a better performance as indicated by C-index of 0.94 (95% confidence interval [CI]: 0.92–0.96) and well-fitted calibration curves. CRKP was independently associated with 30-day mortality. Multivariate Cox regression analysis revealed that age ≥65 years, higher CCI scores, higher Sequential Organ Failure Assessment scores, the presence of respiratory failure, albumin levels ≤30 g/L, and non-appropriate treatments in 3 days, were associated with 30-day mortality. Conclusion The predictive nomogram established in this study can facilitate the clinicians to make better clinical decisions when treating patients with KP infection.